Resilience of Sudanian: savanna-woodlands in Burkina Faso - Savadogo, P.; Tiveau, D.; Sawadogo, L.; Zida, D.; Dayamba, Sidzabda Djibril (Stellenbosch University, 2011)
The savanna-woodlands of West Africa have been subject to disturbance by fire, grazing and tree cutting for centuries. Often the disturbance is severe, for instance when a thick patch of 4 m tall perennial grass catches fire late in the dry season or man decides to clear-cut an area. Fortunately Mother Nature is very forgiving and the woodlands show remarkable resilience. Research plots were established in the Laba and Tiogo State forests in Burkina Faso in 1992. The plots have been monitored by research institutions from Burkina Faso and Sweden ever since. The results show great inter-annual variation in grass species richness, abundance and diversity at both sites. The combined effects of fire, grazing and tree cutting were limited and varied between life forms. Grazing tended to favor diversity of perennial grasses and fire affected the richness of annual grasses. The herbaceous biomass was reduced by the presence of livestock but the effect was not statistically significant for early fire or selective tree cutting. Fire had a homogenizing effect at the species level with increased biomass of the most abundant annual grass Loudetia togoensis and decreased biomass of the most abundant perennial grass Andropogon gayanus. Fire, grazing and selective tree cutting acted independently on the population dynamics of tree saplings. Many responses are site or species specific which accentuates the importance of landscape-level approaches to understand the impacts of disturbance on structure and function of the savanna ecosystems. The lack of treatment results at some levels clearly show how resilient the woodlands are to disturbance.